2016
DOI: 10.5688/ajpe8010176
|View full text |Cite
|
Sign up to set email alerts
|

Introduction and Assessment of a Blended-Learning Model to Teach Patient Assessment in a Doctor of Pharmacy Program

Abstract: Objective. To integrate a blended-learning model into a two-course patient assessment sequence in a doctor of pharmacy (PharmD) program and to assess the academic performance and perceptions of enrolled students. Design. A blended-learning model consisting of a flipped classroom format was integrated into a patient assessment (PA) course sequence. Course grades of students in the blended-learning (intervention) and traditional-classroom (control) groups were compared. A survey was administered to assess studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
6
26
0
Order By: Relevance
“…Participant satisfaction with the quality of the learning experience is of fundamental importance when evaluating the effectiveness of any teaching method for pharmacy education [7,8]. The results of this review suggest that e-learning satisfies this minimum requirement and that, when compared to more traditional teaching methods, e-learning offers increased convenience, [10,12,17,21,28,29,38,52,56] learning [12,17,21,28,29,52,56,58,60] and the ability to use class time more effectively [20,33,35,50,55,57,63]. These unique advantages clearly establish a role for e-learning within pharmacy education, but it is the disadvantages of e-learning that help to define what this role may be.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Participant satisfaction with the quality of the learning experience is of fundamental importance when evaluating the effectiveness of any teaching method for pharmacy education [7,8]. The results of this review suggest that e-learning satisfies this minimum requirement and that, when compared to more traditional teaching methods, e-learning offers increased convenience, [10,12,17,21,28,29,38,52,56] learning [12,17,21,28,29,52,56,58,60] and the ability to use class time more effectively [20,33,35,50,55,57,63]. These unique advantages clearly establish a role for e-learning within pharmacy education, but it is the disadvantages of e-learning that help to define what this role may be.…”
Section: Discussionmentioning
confidence: 99%
“…The positive reaction in the remaining studies was primarily satisfaction with the effectiveness of the e-learning methods and quality of the learning experience provided. Studies also identified a number of advantages of e-learning, which include increased convenience [10,12,17,21,28,29,38,52,56], the ability to protect 'in class time' [20,33,35,50,55,57,63], the empowerment of students to take responsibility for their own learning [17,20,33,35,50,56,57,63] found the e-learning intervention to be effective in increasing the knowledge or skills of the participants. In 2 of the 3 studies that did not have a positive outcome, Weaver et al, [34] and DeMella et al, [62] examined the delivery of a blended health policy course and an online ethics course, respectively, to pharmacy students.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Rovai and Jordan opinion, half-face learning is a kind of flexible approach in training programs which is com-posed of learning at different times and places to support some of the features of virtual presence in training offers (4). Learning communities are able to put new multidimensional relationships (personal and academic) with learners in learning concepts so that being extensible beyond time, space, and limited courses (5).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they have access to content at any time, so this method makes data accessibility much easier (8). In blended approach, education is done with holistic attitude towards learner by taking his/her personal characteristics such as beliefs, attitudes, knowledge, skills and mental abilities into consideration (4).…”
Section: Introductionmentioning
confidence: 99%